THE EMERGENCE OF HIZBUT TAHRIR INDONESIA (HTI) IN SUPPORTING TO PALESTINE - Abdul Mujib (Institut Agama Islam Ngawi, 2023)
This paper examines the paradox inherent in Hizbut Tahrir Indonesia's (HTI) stance on Palestinian solidarity within the context of globalization. HTI, as a transnational Islamist organization, ideologically opposes globalization as a Western-driven project that fosters poverty and cultural imperialism. Yet, in mobilizing support for Palestine, HTI inevitably appropriates the very mechanisms of globalization, including digital media, internet platforms, weekly bulletins (Al-Waie), and large-scale public demonstrations to disseminate its caliphate ideology. The paper poses two central questions: why does HTI conduct its support for Palestine, and how does it utilize modern media, a product of globalization to advance its objectives? The paper argues that HTI's support for Palestine is driven by a dual motivation: Islamic theological solidarity rooted in the defense of al-Aqsa Mosque and the concept of ummah, and a broader resistance to Western geopolitical hegemony. HTI rejects the human rights framing of the conflict as a Western manipulation designed to suppress the religious imperative of jihad, while simultaneously exploiting the globalized media landscape to amplify its counter-narrative and coordinate transnational mobilization. The paper further analyzes how HTI's caliphate project faces structural limitations within Indonesia's Pancasila state framework, an imagined community whose pluralist foundations are incompatible with HTI's universalist Islamic polity. The case concludes by demonstrating that HTI's position exemplifies Giddens' thesis that globalization is not a system one can choose to reject, it is an inexorable structural condition of modernity that reshapes even the most determined of its opponents. The banning of HTI in Indonesia in 2017 confirms these structural limits, yet HTI's theological framing of Palestine continues to shape Indonesian Islamic public discourse.